Association of Indoor Tanning Exposure With Age at Melanoma Diagnosis and BRAF V600E Mutations. (28th March 2019) - Burbidge, Toni E; Bastian, Boris C; Guo, Danny; Li, Haocheng; Morris, Don G; Monzon, Jose G; Leung, Gabriella; Yang, Huiming; Cheng, Tina
Abstract: There is limited information on how indoor tanning promotes melanoma development. We investigated indoor tanning use in patients with melanomas in sun-exposed skin and studied the clinicopathological and molecular characteristics in relation to indoor tanning exposure. Patients from a multidisciplinary clinic for cutaneous cancers completed standardized questionnaires on risk factors for melanoma as a component of medical history at their initial consultations. For this study, we included patients from December 2013 to May 2015. The 114 patients who reported indoor tanning exposure were younger at diagnosis than the 222 patients who did not (51.5 vs 64.0 years, two-sided P < .001). BRAF V600E genotype was more prevalent in ever-users than in nonusers (42.9% vs 28.3%, two-sided P = .04) and higher in ever-users who initiated indoor tanning prior to age 25 years compared with age 25 years or older (62.2% vs 31.1%, two-sided P = .003). There were more melanomas in intermittently sun-exposed skin in ever-users than nonusers (65.7% vs 51.9%, respectively, two-sided P = .02). Our data suggest indoor tanning may promote melanomas that arise in skin with low-chronic sun-induced damage through BRAF V600E-mediated melanomagenesis.